Menyama Braya dalam Masyarakat Bali (Perspektif Pendidikan Agama Hindu) - Sukariawan, Putu (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2024)
Hindu religious education must be taught to become a guide to life that contains many values ​​and norms that will help people live in all things, including their relationship with Sang Hyang Widhi, fellow humans, and their environment. Menyama braya, meaning "brother", is a well-known social value system in Hindu Bali. The concept of equaling braya is a strong foundation in building harmony and implementing respect between religious communities. This research uses a purposive technique, which means that subjects are selected based on research objectives so that informants can provide the necessary information and aim to obtain the necessary and valid information. Data collection in this research refers to the principle that the researcher is the main tool for conducting research which is used objectively and in accordance with the research objectives. Researchers will also collect data through interviews, observation and documentation with appropriate methods, researchers can obtain accurate results and can help in decision making or policy making in the future. In this research, to analyze Menyama Braya in Balinese Society, perfect Hindu Religious Education in its analysis discusses Menyama Braya in the Balinese Community, namely building social harmony and togetherness between fellow citizens in society. There are many religious and cultural values ​​contained in this tradition, especially in relation to Hindu religious education. The function of Hindu religious education is in the menyama braya tradition in the Balinese community which emphasizes building togetherness, developing local culture and traditions, fostering harmony. The Value of Hindu Religious Education in Embracing Braya in the Balinese Community. The value of Hindu religious education plays an important role in preserving and strengthening the concept of Menyama Braya in Balinese society. These religious values ​​emphasize the importance of unlimited brotherhood, helping each other and maintaining balance, respect, and commitment to environmental cleanliness.